CSR Investment Strategy for Live-Streaming Supply Chain Considering Consumer Preference - Guohu Qi; Suqin Sun; Xuemei Zhang; Zhi Liu; Juan Tang (Systems)
Live streaming has been widely used by enterprises to motivate consumers in real-time interactions. However, live streamers’ corporate social responsibility (CSR) has been overlooked in existing studies. This paper examines the CSR investment strategy for the brand owner and live streamer considering the effect of consumer preference and power structure within live-streaming supply chains (LSSCs). To achieve this objective, we develop different Stackelberg game models to examine CSR investment strategy in an LSSC by focusing on whether either firm can be the LSSC leader or invest in CSR. Additionally, the impact of CSR investment strategy on consumers and both firms of LSSC investing in CSR are analyzed. Our findings reveal that regardless of who the LSSC leader or CSR investor is, CSR investment benefits both LSSC firms, and the LSSC leader (brand owner or live streamer) always benefits more from investing in CSR. However, the LSSC follower investing in CSR benefits consumers. Moreover, either one of the LSSC firms prefers the other firm to invest in CSR when consumer sensitivity is low; otherwise, it prefers investing in CSR by itself. Finally, our research highlights that both firms investing in CSR can achieve win-win outcomes for LSSC members and consumers. These findings provide implications for LSSC firms in CSR investment strategies considering different consumer preferences.